2021
DOI: 10.1186/s12906-021-03256-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of pharmacists in complementary and alternative medicine in Lebanon: users’ perspectives

Abstract: Background Customers’ expectations and satisfaction are critical to ensure a more effective role of the community pharmacists in promoting the safe use of Complementary and Alternative Medicine (CAM). The aim of this study is to examine the perceptions and practices of customers buying their CAM products from pharmacies and explore their satisfaction with CAM-related services offered by the community pharmacists in Lebanon. Methods A national cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
1
7
0
2
Order By: Relevance
“…Furthermore, our results pointed out that NS use was associated with attending campaigns and relying on pharmacists for DS information. This result was similar to that of a recent study (36) highlighting…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our results pointed out that NS use was associated with attending campaigns and relying on pharmacists for DS information. This result was similar to that of a recent study (36) highlighting…”
Section: Discussionsupporting
confidence: 93%
“…For example, in the study by Kwan et al, participants believed that some pharmacists were not knowledgeable about HDSs and expressed concerns about their ability as gatekeepers to consumer safety [ 41 ]. In a study in Lebanon, Hijazi et al, reported that the majority of consumers (61.3%) did not regard CPs as more knowledgeable about HDSs than other HCPs [ 46 ]. Furthermore, in previous studies involving pharmacists in various countries such as the U.S., Australia, Thailand, Singapore, and Malaysia, many pharmacists have been reported to have inadequate knowledge about HDSs [ 34 , 40 , 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survey instrument was developed based on an extensive literature review. Research articles discussing the reasons for consultation with pharmacists around HDS use [ 40 , 41 , 44 , 45 , 46 , 47 ], pharmacist- or HCP-patient communication and relationship [ 48 , 49 ], and complementary medicine disclosure to HCPs [ 50 , 51 , 52 ] were used. Based on the literature review, the consultation and non-consultation with CPs about HDSs can be influenced by the consumers’ perceptions of the consultative roles of CPs with respect to HDSs, facilitators (e.g., having a good relationship with CPs, having adequate time to consult CPs, willingness of CPs to spend time providing consultation, etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kuwait, people still have negative perceptions regarding community pharmacists [ 11 ]. In Lebanon, two studies [ 12 , 13 ] revealed that the public perception towards the role of the community pharmacists is still poor, despite the presence of registered pharmacists.…”
Section: Introductionmentioning
confidence: 99%